2003
DOI: 10.1136/gut.52.7.966
|View full text |Cite
|
Sign up to set email alerts
|

Severe idiopathic gastroparesis due to neuronal and interstitial cells of Cajal degeneration: pathological findings and management

Abstract: Gut 2003;52:966-970 Delayed gastric emptying can be due to muscular, neural, or humoral abnormalities. In the absence of an identified cause, gastroparesis is labelled as idiopathic. We present the case of a patient with severe idiopathic gastroparesis. Pharmacological approaches failed, as well as reduction in gastric emptying resistance with pyloric injection of botulinum toxin and pyloroplasty. Therefore, subtotal gastrectomy was performed. Histological and immunohistochemical study of the resected speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
92
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(101 citation statements)
references
References 26 publications
(18 reference statements)
7
92
0
2
Order By: Relevance
“…We found, using a different cohort of patients from the previously reported study from the gastroparesis clinical research consortium, 13 that there was a decrease in ICC numbers in the circular muscle of gastroparetic samples compared to controls. This is in agreement with a growing number of human studies that show similar levels of loss of ICC in both diabetic and idiopathic gastroparesis 14,[33][34][35][36][37][38][39][40] and a correlation between the degree of ICC loss and gastric emptying in diabetic gastroparesis. 15 The main finding of this study is that there was a significant correlation between number of ICC and CD206 numbers in diabetic gastric tissue and diabetic gastroparetic tissue.…”
Section: Discussionsupporting
confidence: 91%
“…We found, using a different cohort of patients from the previously reported study from the gastroparesis clinical research consortium, 13 that there was a decrease in ICC numbers in the circular muscle of gastroparetic samples compared to controls. This is in agreement with a growing number of human studies that show similar levels of loss of ICC in both diabetic and idiopathic gastroparesis 14,[33][34][35][36][37][38][39][40] and a correlation between the degree of ICC loss and gastric emptying in diabetic gastroparesis. 15 The main finding of this study is that there was a significant correlation between number of ICC and CD206 numbers in diabetic gastric tissue and diabetic gastroparetic tissue.…”
Section: Discussionsupporting
confidence: 91%
“…A reduction in the volume of the ICC or damage to their process has been reported in almost every clinical motility disorder that has been investigated, including Hirschsprung's disease (89,90,173), chronic constipation (198), slow-transit constipation (7,67,189), megacolon (189), gastroparesis (199), diabetic mellitus (108), inflammatory bowel disease, animal models of inflammation (102,122,127), pyloric stenosis (92,172,195), achalasia (56,61,63), and chronic idiopathic intestinal obstruction (81,156). However, there are little or no data to correlate the abnormalities of specific subtypes of ICC with specific features of motility dysfunction or clinical symptoms.…”
Section: Icc In Gastrointestinal Motility Disordersmentioning
confidence: 99%
“…Ordog et al [14] suggest that damage to interstitial cells of Cajal may play a key role in the pathogenesis of diabetic gastropathy. Meanwhile, Zarate et al [15] reported that histological and immunohistochemical study of the resected specimen showed hypoganglionosis, neuronal dysplasia, and marked reduction in both myenteric and intramuscular interstitial cells of Cajal in patients with idiopathic gastroparesis. Certainly, PGS after gastric surgery also can be due to muscular, neural, or humoral abnormalities.…”
Section: Discussionmentioning
confidence: 99%